Workload Influence on Employee Performance of Aria Villas Seminyak with Work Stress as a Variable Intervening - Setiti, Luh Made Dian; Paramarta, Wayan Arya (GREENOMIKA, 2023)
This study aims to determine how the influences of workload on employee performance with work stress as a variable intervening on employee of Aria Villas Seminyak. This study used all population because the total of employee only 40 people and this study called study on population. From 40 employee only 32 responses the questionnaire. The research data analyzed by Smart PLS version 4.0.9 program. The results of this study conclude that workload has a positive and significant effect on work stress, workload has a positive and significant effect on employee performance, work stress has a negative and insignificant effect on employee performance and workload has a negative and insignificant effect on employee performance through work stress.